Violencia obstétrica: reproduciendo el dolor (2021)
This article proposes to analyzes obstetric violence as a form of gender violence that acts in relation to a structural discrimination and violence against women in Colombia. In order to develop this objective, a critical documentary review of a qualitative and socio-legal point of view was chosen, applied to clinical, legal and scientific elements that account for the implications of the discriminatory and violating actions perpetrated against pregnant women from the interrelationships with institutions such as the legal or political. Finally, the need to implement legal and political resources for the protection of pregnant women is presented within the process of developing gender perspective in Colombia.